Gastro-oesophageal reflux and aspiration of gastric contents in adult patients with cystic fibrosis. Issue 8 (27th March 2008) - Blondeau, K; Dupont, L J; Mertens, V; Verleden, G; Malfroot, A; Vandenplas, Y; Hauser, B; Sifrim, D
Abstract : Background: Gastro-oesophageal reflux (GOR) is increased in cystic fibrosis (CF), but its prevalence, characteristics, association with gastric aspiration and respiratory impact are not well characterised. We investigated acid and weakly acidic reflux, aspiration and respiratory symptoms/function in adult CF patients. Methods: Thirty-three CF patients [19 men; 29 (18–55) years, [10 post-lung transplant (LTx)] underwent impedance–pH monitoring for detection of acid (pH<4) and weakly acid GOR (pH 4–7). In 16 patients cough was objectively recorded with oesophageal manometry, and the symptom association probability (SAP) was calculated. Saliva and bronchoalveolar lavage fluid (BALF) were tested for bile acids. Results: Twenty-eight patients had increased GOR (21 acid, 5 weakly acidic and 2 acid+weakly acidic) and 10 had a positive SAP for reflux cough. GOR parameters were similar in non-LTx and post-LTx CF patients. The sequence reflux cough was significantly more common than cough reflux. Sixteen of 38 patients had bile acids in saliva and 6/10 in BALF and this was almost exclusively observed in patients with genotype DF508/DF508. Only 12/28 with increased GOR and 9/22 with bile acids in saliva/BALF had typical reflux symptoms. There was a positive correlation (r = 0.53, p = 0.03) between oesophageal acid exposure and cough. SAP-positive patients with for reflux cough had a lower lung function than SAP-negative patients. Conclusion: Increased GOR is prevalent in CF and not secondary to cough. Acid GOR is common, but weakly acidic GOR may also occur. CF patients have a high risk of aspiration and reflux seems to be associated with more cough and poorer lung function. Outcome studies with intense anti-reflux therapy are needed to confirm the deleterious role of reflux in CF progression.